Muscle fiber conduction velocity in situ revisited: A new approach to an ancient technique - Kouyoumdjian, João Aris; Graca, Carla Renata (Frontiers in Neurology, 2023)
The aim here is to measure the muscle fiber conduction velocity (MFCV) in situ in the Tibialis Anterior muscle in healthy subjects. Thirty-six subjects matched for age and sex were studied. The MFCV was measured with a concentric needle by intramuscular monopolar needle electrical activation at a distance of 50 mm. The mean consecutive difference (MCD) < 5 µs was obtained after a median of 62 muscle fiber action potentials (MFAPs), confirming a direct muscle fiber activation. The measuring latency was at the median point of ascending depolarizing line of the MFAP. The calculated MFCV from 784 MFAPs were 4.10 ± 0.66 m/s, 3.99 ± 0.57 for females (95%, 2.85 to 5.13), and 4.20 ± 0.73 for males (95%, 2.74 to 5.67). The MFCV was 5.22% faster in males. The calculated fast-to-slow MFCV ratio (F/S ratio) was 1.47 for females (95%, 1.27 to 2.54) and 1.67 for males (95%, 1.31 to 3.74). Aging significantly increased the F/S ratio. As the MFCVs mainly depend on muscle diameter, their assessment is a quick and helpful tool for estimating it. Its variability by the F/S ratio also is a powerful tool in the follow-up of some neuromuscular disorders.